Объяснение:
( x + 2 ) ^ 4 - 4 * ( x + 2 ) ^ 2 - 5 = 0 ;
Пусть ( х + 2 ) ^ 2 = а, тогда:
а ^ 2 - 4 * a - 5 = 0 ;
a1 = ( 4 - √36 ) / ( 2 * 1 ) = ( 4 - 6 ) / 2 = - 2 / 2 = - 1 ;
a2 = ( 4 + √36 ) / ( 2 * 1 ) = ( 4 + 6 ) / 2 = 10 / 2 = 5 ;
Тогда:
1 ) ( x + 2 ) ^ 2 = - 1 ;
x ^ 2 + 4 * x + 4 = - 1 ;
x ^ 2 + 4 * x + 4 + 1 = 0 ;
x ^ 2 + 4 * x + 5 = 0 ;
Нет корней ;
2 ) ( x + 2 ) ^ 2 = 5 ;
x ^ 2 + 4 * x + 4 = 5 ;
x ^ 2 + 4 * x - 1 = 0 ;
x1 = ( -4 - √20 ) / ( 2·1 ) = -2 - √5 ;
x2 = ( -4 + √20 ) / ( 2·1 ) = -2 + √5 ;
ответ: х = -2 - √5 и х = -2 + √5
1) Выразим каждый множитель как одночлен в квадрате.
0,01 – это 0,1²
a⁶ - это (а3)2
b⁴ - это (b2)2
Получается, что 0,01a⁶b⁴ = 0,1² × (а3)2 × (b2)2 = (0,1а3b2)2
ответ: 0,01a⁶b⁴ = (0,1а3b2)2
2) Выразим каждый множитель как одночлен в квадрате.
9 = 32
b⁴ = (b2)2
c⁸ = (c4)2
Получается, что 9b⁴c⁸ = 32 × (b2)2 × (c4)2 = (3b2c4)2
ответ: 9b⁴c⁸ = (3b2c4)2
3) Выразим каждый множитель как одночлен в квадрате.
100 = 102
p² = p2
q⁶ = (q3)2
Получается, что 100p²q⁶ = 102 × p2 × (q3)2 = (10pq3)2
ответ: 100p²q⁶ = (10pq3)2